Post-SSRI sexual dysfunction and SSRI induced sexual dysfunction - literature review - Panek, Eliasz; Jasłowski, Damian; Rzeszutko, Mateusz; Raczkiewicz, Przemysław; Panasiuk, Dominika; Skrętowicz, Mateusz; Szponarowicz, Patrycja; Snopkowski, Bartosz; Korzec, Tomasz; Sosnowski, Jakub (Journal of Education, Health and Sport, 2023)
Introduction: Selective serotonin reuptake inhibitors (SSRIs) are one of the most commonly used drugs. One of the most common side effects are those related to sexual function. We can divide them into sexual dysfunction occurring during the use of SRRIs and those occurring and persisting after discontinuation of SSRIs. Purpose: To review available PubMed data on SSRI-related sexual dysfunction, epidemiology, symptoms and treatment. Current state of knowledge: SSRIs are first-line drugs for depression and other mental disorders. Their use can cause sexual dysfunction. SSRI-induced sexual disorders are more common but easier to treat. Post-SSRI sexual dysfunction is less common and harder to treat. There are several hypotheses regarding its pathomechanism, such as epigenetic changes, serotonin neurotoxicity, endocrine disruption, and downregulation of serotonin receptors. Conclusions: Sexual dysfunction after SSRIs left without treatment increases the chances of self-discontinuation of drugs by patients and contributes to significant suffering. In the case of SSRIs induced sexual dysfunction, there are several possible interventions that can effectively eliminate sexual dysfunction and restore the patient’s comfort. There are no effective treatments for post-SSRI sexual dysfunction syndrome. In addition, the diagnosis of PSSD is difficult as there are no specific diagnostic criteria. More research is needed to determine how to diagnose and treat patients who develop PSSD.